Broadband, partially unilateral active testset for network analyser. Issue 14 (1st July 2016) - Ghosh, D.; Kumar, G.
Abstract : This Letter describes the design of a broadband testset which measures the reflection coefficient of an arbitrary load. The designed testset has four ports. The first port is for an RF input and the second is for the unknown load, while the remaining two ports are for a reflected power detector and a reference power detector, respectively. The testset adopts a divider‐combiner configuration and makes use of differential amplifier and compact, broadband two section power combiners to realise port matching networks at the intermediate stage and for phase cancellation at the last stage. The good phase cancellation is shown to result in high isolation over a broad frequency range. The testset achieves high load dynamic range from 28 to 35 dB in the frequency range of 500 MHz to 3 GHz. The high dynamic range over a broad bandwidth makes the designed testset suitable for use in network analysers.